From vulnerability to resilience: unraveling the role of oxidative stress in preterm brain injury - Qianqian Jiang; Jialin Wen; Yingxue Ding; Hong Cui (Italian Journal of Pediatrics)
Abstract Neonatal medicine advancements have significantly improved preterm infants’ survival rates, yet optimizing their neurodevelopmental outcomes, is challenging. A central factor in these challenges is oxidative stress (OS), arising from an imbalance between free radicals (FRs) production and antioxidant defense mechanisms. In preterm infants, OS is particularly detrimental due to their underdeveloped antioxidant systems, high brain metabolic demands, immature blood-brain barrier (BBB), and increased vulnerability to inflammation and hypoxia. This review focuses on the multifaceted aspects of OS concerning preterm brain injury. It examines developmental, physiological, pathological, and environmental factors contributing to preterm infants’ susceptibility to OS. In addition, the review discusses various pathophysiological mechanisms of preterm brain injury and proposes comprehensive solutions, including the use of antioxidants, nutritional support with a focus on breast milk, tailored oxygen therapy, and the importance of reducing oxidative stressors in the neonatal intensive care unit (NICU) including effective pain management and environmental modifications. The review emphasizes the need for future research focused on developing integrated and individualized treatment approaches for brain injury in preterm infants. Specifically, a deeper understanding and effective management of OS is crucial for enhancing long-term prognoses in this vulnerable group.